PENGARUH BOPO, NPL, NIM, CAR DAN LDR TERHADAP KINERJA KEUANGAN PERBANKAN(Studi kasus pada Bank yang terdaftar di BEI) - Purwoko, 10.42.02.0092 Didik (Students Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of ROA, NPL, NIM, CAR and LDR on ROA, as a proxy of the financial performance of the banking company. The data used in this study were obtained from the Companys Financial Statements Banking Publications listed on the Stock Exchange. Based on purposive sampling, sample worth using as many as 28 of Banking Companies with the following criteria: Banking Company is listed on the Indonesia Stock Exchange (BEI), never in the Delete and provide financial statement data for the period 2007-2010. The type of data used are secondary data. Technical analysis is normality test, the assumptions of classical and multiple linear regression based on combined data time series and cross section. The results showed that the variables ROA and significant negative effect on ROA, NPL significantly and negatively related to ROA, NIM has positive and significant impact on ROA, CAR and LDR has not significant impact on ROA. Bank financial performance is influenced by a variable dependent variable ROA, NPL, NIM, CAR and LDR of 73.1% while the remaining 26.9% is explained by other causes outside the model. Keywords: Efficiency of Operations (ROA), credit risk (NPL), Market Risk (NIM), Capital (CAR), Liquidity (LDR) and Bank Financial performance (ROA). Â